Study of aeration efficiency at stepped channels - Baylar, A; Emiroglu, ME (Thomas Telford Services Ltd, 2003)
The oxygen concentration in surface waters is a prime indicator of the quality of that water for human use as well as use by the aquatic biota. Hydraulic structures can increase dissolved oxygen levels by creating turbulent conditions where small air bubbles are carried into the bulk of the flow. Stepped channels are a particular instance of this, and the aeration efficiency of such structures has not been studied in the laboratory or the field. This paper studies stepped channels having different length/height ratios and step heights and their effects on the aeration performance. A regression equation predicting the aeration efficiency was developed for stepped channels. The results demonstrated that L/h and step height had a significant effect on the aeration efficiency of stepped channels. Aeration efficiency generally increased with increasing step height and with decreasing L/h.
Keywords: hydraulics & hydrodynamics; hydrology & water resources; water supply